Pengaruh Jenis Media Tanam Terhadap Pertumbuhan dan Hasil Tanaman Kale (Brassica oleracea var. acephala) Pada Hidroponik Sistem Wick - Femia Emilga; Darso Sugiono; Rommy Andhika Laksono (Jurnal Ilmiah Wahana Pendidikan, 2022)
Kale are plants that have a variety of nutrients that are good for the body, but there is a land function change that causes land to be cultivated is decreasing which is a production problem that can be overcome using the hydroponics wick system. This study aims to obtain the best treatment of the type of planting media for the growth and yield of kale plants (Brassica oleracea var. Acephala) on the hydroponics of the wick system. The research was carried out at the Telaga Desa screen house located in the KIIC Industrial Estate, Telukjambe Timur District, Karawang Regency from May to June 2022. The research method used was an experimental method with a single-factor group Randomized Block Design (RBD) environment design consisting of 8 treatments with 3 tests. The data is analyzed with a variety analysis and if the F test of 5% level shows significantly different results, it will be continued with the DMRT (Duncan Multiple Range Test) test at a level of 5%. The treatment of the type of husk charcoal media + peatmoss ratio (2: 1) gave the highest yield on the average plant height of 28.13 cm, on the number of leaves which was 18.79 strands, in the stem diameter which was 6.51 mm, on the leaf area of 64.80 cm², at the root length of 37.03 cm, and the fresh weight of the roots was 20.19 grams.